Silk Nanocrack Origami for Controllable Random Lasers (Adv. Funct. Mater. 45/2021). (1st November 2021) - Dogru‐Yuksel, Itir Bakis; Jeong, Chanho; Park, Byeonghak; Han, Mertcan; Lee, Ju Seung; Kim, Tae‐il; Nizamoglu, Sedat
Abstract : Silk Nanocrack Origami In article number 2104914, Tae‐il Kim, Sedat Nizamoglu, and co‐workers demonstrate directional random lasers by using the ancient art of origami. The folding of silk fibroin paper introduces nanocracks that are orthogonal to the folding direction, and the nanocrack‐silk boundaries enable oscillation of light by diffuse reflection and lead to laser light generation.